Optimalisasi Kreativitas Siswa dalam Pembelajaran IPA melalui Penerapan Tugas Komik - Qadariah, Nosi (Program Studi Pendidikan Biologi, 2024)
This research aims to optimize students' creativity in learning Natural Sciences (IPA) through the implementation of comic-based assignments. The background of this study is based on observations at MTs S PPM DINIYYAH PASIA, Agam Regency, West Sumatra, which identified several issues in science learning, such as the lack of learning resources, limited use of gadgets, and low student reading interest. This research employs the Classroom Action Research (CAR) method with the Kemmis and McTaggart model, encompassing the stages of planning, action, observation, and reflection. The results indicate a significant increase in students' creativity scores after the implementation of comic-based assignments, with the average creativity score rising from 61.6 (low category) to 91.02 (very good category). Effective strategies for optimizing the implementation of comic-based assignments include the integration of IPA materials with comics, the use of diverse media, intensive mentoring, student collaboration, regular evaluation and reflection, and rewarding the best works.